2006
DOI: 10.1029/2006gl025928
|View full text |Cite
|
Sign up to set email alerts
|

Increase of shear wave velocity before the 1998 eruption of Merapi volcano (Indonesia)

Abstract: We infer temporal changes in the elastic properties of the edifice of Merapi volcano (Java, Indonesia) before its eruption in 1998 by analyzing multiply scattered elastic waves excited by a repeatable controlled seismic source. A pre‐eruptive increase of shear wave velocity, which correlates well with pre‐eruptive seismicity and dome‐growth is revealed. The method can be used as a “pressure‐gauge” for pressure changes inside of volcanoes, because increasing pressures in rocks are known to cause proportionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 15 publications
1
72
1
1
Order By: Relevance
“…It is evident that the most reliable results can be obtained by inverting the data subsets with identical seismic ray paths generated by the same seismic sources to the same receivers in repeated experiments (e.g., Wegler et al, 2009). Such experiments can be conducted by fixing seismometer positions and repeated artificial sources, such as man-made explosions (e.g., Li et al, 2006), air-guns fired in water basins (e.g., Wegler et al, 2006) or vibrator sources (e.g., Ikuta et al, 2002), but making such studies is very expensive. It is also suggested to use the coda of similar or repeated earthquakes (earthquake multiplets) to extract the temporal variations in seismic velocity Random noises with zero mean and a standard deviation of 0.3 s and 5 km were added to the origin times (a-d) and the latitudes (f-i), respectively, to account for the uncertainties in the hypocenter parameters.…”
Section: Discussionmentioning
confidence: 98%
“…It is evident that the most reliable results can be obtained by inverting the data subsets with identical seismic ray paths generated by the same seismic sources to the same receivers in repeated experiments (e.g., Wegler et al, 2009). Such experiments can be conducted by fixing seismometer positions and repeated artificial sources, such as man-made explosions (e.g., Li et al, 2006), air-guns fired in water basins (e.g., Wegler et al, 2006) or vibrator sources (e.g., Ikuta et al, 2002), but making such studies is very expensive. It is also suggested to use the coda of similar or repeated earthquakes (earthquake multiplets) to extract the temporal variations in seismic velocity Random noises with zero mean and a standard deviation of 0.3 s and 5 km were added to the origin times (a-d) and the latitudes (f-i), respectively, to account for the uncertainties in the hypocenter parameters.…”
Section: Discussionmentioning
confidence: 98%
“…Iwate, Japan. Wegler et al (2006) observed a shear wave velocity increase before the 1998 Merapi volcano eruption. These studies used earthquake doublets/multiplets or repeating active seismic experiments as sources to observe small seismic velocity changes.…”
Section: Introductionmentioning
confidence: 92%
“…Comparing coda waves from identical sources is a useful method of estimating temporal changes in seismic velocity (e.g., Snieder et al 2002). Seismic velocity changes caused by a large earthquake or volcanic activity have been detected using the cross-correlation of seismograms of repeating earthquakes (e.g., Poupinet et al 1984;Rubinstein and Beroza 2004;Yamawaki et al 2004) and active control sources (e.g., Nishimura et al 2000;Wegler et al 2006). However, because repeating earthquakes do not occur frequently and artificial explosions are expensive, these methods often yield velocity changes with poor temporal resolution.…”
Section: Introductionmentioning
confidence: 99%